Health Status Index Models: A Unified Mathematical View - Torrance, George W. (Management Science, 1976)
A general mathematical formulation of the health status index model is developed. Equations are given for three types of population health indexes and for the determination of the amount of health improvement created by a health care program. Fourteen of the major health status index models from the literature are analyzed, and it is shown that each can be viewed as a special case of the general formulation. It is hoped that the paper will help to unify the health status index concept, will serve to standardize terminology and notation, and will facilitate comparisons of the various models.